Web-Based Expert System for Diagnosing Gastric Disease Using Bayes Theorem Method - Ayu Anggilina; Ade Eviyanti (Procedia of Engineering and Life Science, 2021)
Health is a very expensive thing, so it takes an awareness to protect it. The human body has many limbs, one of which is the stomach. Gastric disease is a disease that cannot be accommodated, because if left untreated it can cause other diseases to arise and can also cause death if it is not immediately supported. Gastric disease can be caused by an inappropriate diet, a burden on the mind and also an infection caused by bacteria. The author took the initiative to create a web-based gastric disease diagnosis expert system using the Bayes theorem method which is useful for gastric disease sufferers in diagnosing their own gastric disease. The method used by researchers is the Bayes theorem method. The data collection technique used is quantitative data techniques. The results that have been achieved from this research are that it can prevent and minimize the risk of gastric disease in sufferers or the community.